Software development reinforced concrete computer design accordance with BS 8110 / Mohd. Tabie Yusof - Yusof, Mohd. Tabie (1990)
The development of a computer aided software of reinforced concrete analysis and design is presented herein. The program has been developed based on British Standard Code of Practice BS 8110 : 1985. This computer software is capable of analysing and designing reinforced concrete elements such as continuous beam, solid slab, column and shallow foundation. The result of this analysis and design can be displayed on the screen or printed as hardcopy. It has been organised efficiently. The software has been developed for the IBM or Compatible Personal Computer System, and it is written in BASIC Language where Microsoft (QuickBASIC) Compiler and Editor Version 4.0 were used.